Inclusive classroom climate development as the cornerstone of inclusive school building: review and perspectives - Margas, Nicolas (Frontiers in Psychology, 2023)
Education institutional guidelines around the world agree that building more inclusive schools is a priority. To meet this objective also addresses important school issues such as bullying, school dropout, students' well-being, and their long-term health. The reality of school practice, however, belies this institutional will. To help fill the gap, this theoretical review documents the value that the construct of classroom climate brings to research and practice in terms of inclusive school development. The article firstly points out that the current main challenge is to develop Inclusive Mainstream Teaching (IMT) in diverse classrooms. Indeed, empirical findings show that IMT is needed in all classrooms to guarantee the effectiveness of special accommodations in schools that are targeted at special education needs students. Empirical evidence also documents that intervening at classroom level is both a pragmatic and powerful way to developing inclusive schooling. However, developing IMT in the classroom remains a challenging issue for both teachers and researchers. The review then documents the central role that classroom climate should play in the development of IMT within the class. More precisely, the factors of classroom climate that are associated with inclusive outcomes are identified. In this way, we highlight how these factors of inclusive classroom climate and the measurements associated with them are efficient tools to guide IMT development. These measures are proximal, sensitive, complementary, and pragmatic indicators of effective IMT. Such indicators are very useful in helping research empirically document effective IMT, ensure that any small improvement is assessed, monitor teachers' progress, and assist their professional growth. Theoretically positioned as a mediator between inclusive teaching in mainstream classrooms and inclusive school outcomes, inclusive classroom climate is a tool that appears to be effective in supporting IMT development and, consequently, in the establishment of more inclusive schools.